Implementation of a cashmere goat breeding program amongst nomads in Southern Iran - Mueller, J.P.; Ansari-Renani, H.R.; Momen, S.M.S.; Ehsani, M.; Alipour, O.; Rischkowsky, Barbara A. (Elsevier, 2015)
A breeding program to improve income from Raeini cashmere herds run by nomads in Southern Iran was implemented. Eight nomads agreed on improving fleece weight, body weight and down yield while reducing cashmere fibre diameter of white coated goats. Economic weights were calculated to define a breeding objective. Each nomad established a breeding nucleus selecting visually his best 40 does and two bucks from about 250 goats. Nomads used different systems to ensure separate mating of nucleus and general herd animals. Nomads were also able to identify the progeny of each buck. Nucleus progenies were recorded for weaning weight and fleece weight. Fleece samples were collected for analyses of down yield and down fibre diameter. General herd male progeny was castrated. Formal selection indices were used to select nucleus male replacements. To construct the indices phenotypic and genetic parameters were taken from project data and published figures. Accuracy of indices ranged 0.47 to 0.66 depending on the traits included. The inferior buck based on progeny index average was replaced by the best young buck available. Other high ranked young bucks were used in the general herd. The breeding program is in its fourth cycle and favourable selection differentials were confirmed for selected bucks in all traits of interests, in particular for down weight and down diameter, 62 g and −0.5 μm, respectively. The expected benefit of the program is about 4.0 USD accumulating per goat and per year. Fleece testing is an issue since the region lacks a fleece testing service. If fleece sampling is discontinued the expected benefit reduces to about 2.8 USD per goat and per year. Circular use of bucks to control inbreeding and participation of additional nomad families are planned for the future. This experience shows that a participatory breeding program can be successfully implemented under nomadic conditions through intensive collaboration of nomad herders, regional extension officers and scientists.